2021
DOI: 10.1002/mabi.202170019
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐Eluting Medical Textiles: From Fiber Production and Textile Fabrication to Drug Loading and Delivery

Abstract: Back Cover: Drug‐eluting medical textiles have been extensively used in various biomedical applications recently due to their cost‐effectiveness and unique physical and chemical properties. Different fiber production, textile fabrication, and drug loading technologies are used to process the biomaterials to three‐dimensional medical textiles that can be used for wound care, tissue engineering, and transdermal drug delivery applications. This is reported by Samaneh Ghazanfari and co‐workers in article number 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…[1][2][3][4][5] For in vivo use, it is necessary that the material surface possesses antibacterial or anti-inflammatory properties due to the risk of postoperative inflammation and invasion of infectious microorganisms. [6][7] Therefore, the development of drug-immobilized PP materials with controlled drug release property is required. However, PP does not have a reactive functional group and exhibits extremely poor interactions with other molecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] For in vivo use, it is necessary that the material surface possesses antibacterial or anti-inflammatory properties due to the risk of postoperative inflammation and invasion of infectious microorganisms. [6][7] Therefore, the development of drug-immobilized PP materials with controlled drug release property is required. However, PP does not have a reactive functional group and exhibits extremely poor interactions with other molecules.…”
mentioning
confidence: 99%
“…In addition, electrospinning, the general method for producing drugsupported nanofibers, cannot be applied to PP because it is insoluble in organic solvents. 7 Hence, surface modification is the prevalent technique utilized for immobilizing drugs on PP fibers. Gupta et al reported excellent results for sustained drug release via graft copolymerization of N-isopropyl acrylamide (NIPAAm) and acrylic acid onto PP NWF surfaces.…”
mentioning
confidence: 99%